Comparative evaluation of marginal accuracy of metal copings fabricated using direct metal laser sintering, computer-aided milling, ringless casting, and traditional casting techniques: An In vitro study - Annu Eliza James; B Umamaheswari; C B Shanthana Lakshmi (Wolters Kluwer Medknow Publications, 2018)
Purpose: The purpose of the study is to determine the amount of marginal discrepancy produced by Co-Cr copings fabricated using various fabrication methods which include direct metal laser sintering (DMLS), computer-aided milling, traditional casting, and ringless casting and compare the values obtained between each fabrication technique and to evaluate if the fabrication technique can produce prosthesis that is within the standards of clinical acceptance of marginal discrepancy. Materials and Methods: Ten metal copings were fabricated by DMLS, computer-aided milling, traditional casting, and ringless casting. Marginal gap at the buccal, lingual, mesial, and distal areas was measured using silicone replica technique. A digital microscope was used to measure the silicone layer. Statistical analysis was done using one-way ANOVA test and post hoc Bonferroni test to test the difference between the fabrication method and categories of measured points, respectively. Results: The values indicate that the marginal gap was least for the copings fabricated using ringless casting followed by traditional casting and DMLS. The widest gap was seen in copings fabricated using computer-aided milling. Analysis of results showed statistically significant difference between copings fabricated using computer-aided milling and traditional casting (P = 0.029 and 0.043 - mesial and distal, respectively) and computer-aided milling and ringless casting (P = 0.002 and 0.001 - mesial and distal, respectively). Conclusion: Even though the marginal gap was found to vary with the fabrication method, all measurements of marginal gap of all groups were well within the standard clinical acceptance of 120 μ.